2003
DOI: 10.1242/jeb.00664
|View full text |Cite
|
Sign up to set email alerts
|

Introductory tail-flick of the Jacky dragon visual display: signal efficacy depends upon duration

Abstract: SUMMARY Many animal signals have introductory components that alert receivers. Examples from the acoustic and visual domains show that this effect is often achieved with high intensity, a simple structure and a short duration. Quantitative analyses of the Jacky dragon Amphibolurus muricatusvisual display reveal a different design: the introductory tail-flick has a lower velocity than subsequent components of the signal, but a longer duration. Here, using a series of video playback experiments wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 64 publications
5
70
0
Order By: Relevance
“…Our strategy for analyzing movement-based signals combines quantitative analyses of the structure of signals and noise (Peters and Evans, 2003a) with signal-detection experiments (Peters and Evans, 2003b). We use a native Australian agamid lizard, the Jacky dragon (Amphibolurus muricatus), as a model system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our strategy for analyzing movement-based signals combines quantitative analyses of the structure of signals and noise (Peters and Evans, 2003a) with signal-detection experiments (Peters and Evans, 2003b). We use a native Australian agamid lizard, the Jacky dragon (Amphibolurus muricatus), as a model system.…”
Section: Introductionmentioning
confidence: 99%
“…We began by considering the properties responsible for signal efficacy in the Jacky dragon tail-flick (Peters and Evans, 2003b). We found that duration was more important than speed in evoking an orienting response, with long signals being most successful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), suggesting that none of them has evolved specifically to have an alerting function (i.e. design for particular efficacy in engaging a visual grasp reflex), as in some other dynamic visual signals (Peters and Evans, 2003). One possible explanation for this may be that the displays contain far more motion in the vertical plane than in the horizontal.…”
Section: Structure Of the Tidbitting Displaymentioning
confidence: 99%
“…Displays can occur in rapid succession, forming a bout. Lizards often modify their displays by adding introductory tail-flicks (Peters and Evans, 2003), or increasing their profile through lateral compression, gular expansion and nuchal crest erection. Previous video playback experiments found that males were sensitive to 'moment-to-moment' variation in the display rate of simulated opponents and the social contingencies governing interactions .…”
Section: Introductionmentioning
confidence: 99%